Augmented video consultations in care homes during the COVID- 19 pandemic: a qualitative study. Issue 4 (2022) - , Lorraine Ochieng; , Vinay Gupta Richard Wong; , Mahan Salehi; Prasad, Rishabh; Ochieng, Bertha; Ochieng, Rebecca; Nijhof, Dewy
No abstract available